Interpretasi Syukur Bagi Pendidik Agama Islam - Luqman Hakim (Institute Agama Islam Al-Qolam Malang, 2022)
Gratitude is one of the conditions for a person to be in high health in the sight of Allah SWT. However, how many humans forget to be grateful for the blessings that actually come. They are complacent and forget the obligations that must be fulfilled. One of the unseen blessings is the blessing of knowledge. An educator needs gratitude as someone who has been given the blessing of knowledge by Allah SWT. One of the gratitude of a teacher is to teach knowledge to his students. In the Holy Qur'an there is a meaning of gratitude. It is interpreted that the way to be grateful is to draw closer to Allah and the favor with trust. The gratitude for educators who have been given the blessing of knowledge is to practice and teach knowledge to others. This article aims to re-examine the meaning of gratitude, as a discourse of knowledge and development in improving the quality of education through improving the quality of its educators.